2022
DOI: 10.1007/s11145-022-10312-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic assessment as a predictor of reading development: a systematic review

Abstract: Assessments of reading and reading-related skills which measure acquired knowledge may pose problems for the prediction of future reading performance. Such static measures often result in floor effects in the early stages of reading instruction, and may be particularly inaccurate predictors for children from culturally and linguistically diverse (CLD) backgrounds. Dynamic assessment (DA), in contrast, focuses on learning potential by measuring response to teaching, and may therefore be a less biased form of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 55 publications
3
18
0
Order By: Relevance
“…In terms of DA-SSK, only one study was included and could therefore not be compared in subgroup analysis. These findings, which provide suggestive evidence for the validity of DAs of PA and decoding in predicting later word reading outcomes are in line with outcomes of Dixon et al's systematic review which found that both DAs of PA and decoding accounted for significant unique variance in later word reading ability (between 1-33% across included studies; Dixon et al, 2022a).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In terms of DA-SSK, only one study was included and could therefore not be compared in subgroup analysis. These findings, which provide suggestive evidence for the validity of DAs of PA and decoding in predicting later word reading outcomes are in line with outcomes of Dixon et al's systematic review which found that both DAs of PA and decoding accounted for significant unique variance in later word reading ability (between 1-33% across included studies; Dixon et al, 2022a).…”
Section: Discussionsupporting
confidence: 82%
“…Although Hunt et al (2022) findings support DA as a reliable measure for identifying DLD, the small number of studies and sample sizes reveal an area of research that requires attention and the need for more focus on multilingual populations. Dixon et al (2022a;2022b) published two papers exploring whether DAs can uniquely predict variance in the growth of a child's reading development beyond SAs, and whether DAs can act as a viable alternative to diagnosing reading disorders in children. In the first study (2022a) the researchers identified 17 studies that used DA to measure reading skills between at least two timepoints.…”
Section: Previous Systematic Reviews In Dynamic Assessmentmentioning
confidence: 99%
See 3 more Smart Citations